Chardonnay Grape Marc Powder Supplementation May Increase Insulin Sensitivity in Obese and Overweight Men and Women - Lee, Fanny; Woodhouse, Leslie; Arvik, Torey; Keim, Nancy (Current developments in nutrition, 2021)
Chardonnay grape marc (CM) is the remaining skins and seeds from winemaking that offers a rich source of phytonutrients. The objective was to evaluate glucose metabolism following the addition of CM to the diet. Overweight or obese men and women with mild hyperlipidemia between 35–65 y were recruited for this double-blinded 16-week crossover study. Subjects consumed 1500mg of 1) microcrystalline cellulose (MCC), 2) high chardonnay seed extract/WellVine™ marc blend (HE) or 3) high WellVine™ chardonnay marc/seed extract blend (HM) in a randomized order. Each intervention arm lasted 3 weeks and included two 3-week washout periods. Following each intervention, fasting blood was drawn and assayed for glucose and insulin. Indexes of insulin resistance (HOMA-IR, McAuley) and insulin sensitivity (QUICKI) were calculated. Data were transformed before conducting analyses, when appropriate. Analyses were conducted with 24 completed subjects and intention to treat (ITT) with 3 subjects who withdrew using linear mixed model ANOVA. In the ITT analysis, fasting glucose and insulin showed a significant main effect of intervention (P = 0.04 and P = 0.03, respectively). For both glucose and insulin, pairwise comparisons showed a significant difference between HM and MCC (P = 0.03 and P = 0.03, respectively). The indexes, HOMA-IR and QUICKI showed a significant main effect of intervention (P = 0.04 and P = 0.03, respectively), whereas there was no effect with the McAuley index. For HOMA-IR and QUICKI, pairwise comparisons showed a significant difference between HM and MCC (P = 0.04 and P = 0.03, respectively). There was an increase in QUICKI, indicating an increase in insulin sensitivity following the HM arm compared to MCC. This has important implications if it is followed up in a larger cohort. Following the HM arm there was also a decrease in fasting insulin and decrease in HOMA-IR compared to the MCC arm; in this case, the magnitude of these changes are not sufficient to suggest improvement in insulin resistance by clinical definitions. This was a proof of concept study, thus future studies should further explore these findings. NIFA Phase II Small Business Innovation Research Grant awarded to Sonomaceuticals, LLC, USDA CRIS 2032–51,530-025–00D.